Toward an Integrated Clinical, Molecular and Serological Classification of Inflammatory Bowel Disease: Report of a Working Party of the 2005 Montreal World Congress of Gastroenterology - Mark S Silverberg; Jack Satsangi; Tariq Ahmad; Ian DR Arnott; Charles N Bernstein; Steven R Brant; Renzo Caprilli; Jean-Frédéric Colombel; Christoph Gasche; Karel Geboes; Derek P Jewell; Amir Karban; et al. (Canadian Journal of Gastroenterology)
The discovery of a series of genetic and serological markers associated with disease susceptibility and phenotype in inflammatory bowel disease has led to the prospect of an integrated classification system involving clinical, serological and genetic parameters. The Working Party has reviewed current clinical classification systems in Crohn’s disease, ulcerative colitis and indeterminate colitis, and provided recommendations for clinical classification in practice. Progress with respect to integrating serological and genetic markers has been examined in detail, and the implications are discussed. While an integrated system is not proposed for clinical use at present, the introduction of a widely acceptable clinical subclassification is strongly advocated, which would allow detailed correlations among serotype, genotype and clinical phenotype to be examined and confirmed in independent cohorts of patients and, thereby, provide a vital foundation for future work.